Whole genome sequencing and phylogenetic analysis of African swine fever virus detected in a backyard pig in Mongolia, 2019 - Hyeon, Ji-Yeon; Tseren-Ochir, Erdene-Ochir; Lee, Dong-Hun; Nahm, Sang-Soep; Gladue, Douglas P.; Borca, Manuel V.; Song, Chang-Seon; Risatti, Guillermo R. (Frontiers in Veterinary Science, 2023)
African swine fever (ASF) is a highly contagious and fatal disease affecting domestic and wild pigs caused by the African swine fever virus (ASFV). Since the first outbreak in China in August 2018, ASF has spread rapidly in Asia. and the first case in Mongolia was confirmed in January 2019. In this study, we report the first whole genome sequence of an ASFV (ASFV SS-3/Mongolia/2019) detected from a backyard pig in Mongolia in February 2019 using whole genome sequencing. We analyzed their phylogenetic relationship with other genotype II ASFVs from Eurasia. The ASFV SS-3/Mongolia/2019 belonged to genotype II (p72 and p54), serogroup 8 (CD2v), Tet-10a variant (pB602L), and IGRIII variant (intergenic region between the I73R/I329L genes). A total of five amino acid substitutions were observed in MGF 360-10L, MGF 505-4R, MGF 505-9R, NP419L, and I267L genes compared to the ASFV Georgia 2007/1 virus. ML phylogenetic analysis of the whole genome sequence showed that the virus shares a high nucleotide sequence identity with ASFVs recently identified in Eastern Europe and Asia and clustered with the ASFV/Zabaykali/WB5314/2020|Russia|2020 virus which was identified at the border between the Russian Federation and Mongolia in 2020. Our results suggest that trans boundary spread of ASF occurred through close geographic proximity.